Two-Step Nucleation Rather than Self-Poisoning: An Unexpected Mechanism of Asymmetrical Molecular Crystal Growth - Ectors, Philipp; Anwar, Jamshed; Zahn, Dirk (Crystal Growth & Design, 2015)
The identification of two step nucleation mechanisms considerably extended our understanding of crystal nucleation. Here, we report an analogous observation of a two-step mechanism but in 2-D for deposition of molecules to a growing crystal face. Using molecular dynamics simulations connected with the Kawska-Zahn approach, extgreeka-resorcinol precipitation from the vapor is treated at the low driving force regime. Growth at the faster growing (01̅1̅) face reveals the deposition of molecules to form a disordered liquid-like layer. Strikingly, this apparently divergent (nonepitaxial) molecular arrangement does not represent self-poisoning which would lower the growth rate of the (01̅1̅) face. On the contrary, more favorable attachment energy along with a disorder–order transition, akin to a two-step nucleation observed in 3-D systems, leads to growth rates that are about 20 times faster than the more standard mode association of molecules at the (011) face where the molecules readily align according to the crystal lattice.
EAM Import::2019-03-13